The Current Role of Interventional Radiology in the Management of Acute Trauma Patient - Luckhurst, Casey M. (Semin Intervent Radiol, 2021)
Trauma is one of the most common causes of death, particularly in younger individuals. The development of specialized trauma centers, trauma-specific intensive care units, and trauma-focused medical subspecialties has led to the formation of comprehensive multidisciplinary teams and an ever-growing body of research and innovation. The field of interventional radiology provides a unique set of minimally invasive, endovascular techniques that has largely changed the way that many trauma patients are managed. This article discusses the role of interventional radiology in the care of this complex patient population, and in particular how the specialty fits into the overall team management of these patients.